Observations of Pole-to-Pole, Stratosphere-to-Ionosphere Connection - Goncharenko, L. P.; Harvey, V. L.; Randall, C. E.; Coster, A. J.; Zhang, S.-R.; Zalizovski, A.; Galkin, I.; Spraggs, M. (Frontiers in Astronomy and Space Sciences, 2022)
The behavior of the Earth’s middle atmosphere and ionosphere is governed by multiple processes resulting not only from downward energy transfer from the Sun and magnetosphere but also upward energy transfer from terrestrial weather. Understanding the relative importance of mechanisms beyond solar and geomagnetic activity is essential for progress in multi-day predictions of the Earth’s atmosphere-ionosphere system. The recent development of research infrastructure, particularly in Antarctica, allows the observation of new ionospheric features. Here we show for the first time that large disturbances observed in the Arctic winter polar stratosphere (20-50 km above ground and at 60-90oN) during a sudden stratospheric warming event are communicated across the globe and cause large disturbances in the summertime ionospheric plasma over Antarctica (60-90oS). Ionospheric anomalies reach ~100% of the background level and are observed for multiple days. We suggest several possible terrestrial mechanisms that could contribute to the formation of upper atmospheric and ionospheric anomalies in the southern hemisphere.